Analysis of the Maximum Seismic Intensity Through the Theory of Extreme Values - Pérez, Jonathan Alfonso (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2022)
The objective of this study was to analyze the seismic behavior of the Pacific Region of Colombia. For the development of the study, local seismic magnitudes of the departments of Chocó, Valle del Cauca, Cauca, and Nariño were included between the years 1993 and 2018. In this sense, and through the extreme value theory, the maximum magnitudes in the seismic events that occurred were analyzed to obtain models that describe the behavior of the observations by using the method of maximum blocks and threshold exceedances, which allows the magnitudes to be associated of each of the departments to a type of distribution such as: Gumbel, Weibull or Frechet, from the Widespread Distribution of Values or Beta, Exponential or Pareto with use of the Generalized Pareto Distribution. The results obtained show return levels of 5.08, 6.03, 6.88 and 7.24 for the return periods of 2, 10, 50 and 100 years, respectively, for the department of Chocó using the maximum block method (Gumbel). Likewise, using the method of threshold exceedances (Exponential), it is estimated that, in 100 years, earthquakes of magnitude equal to or greater than 7.2 on the Richter scale may occur in Chocó.